Imaging colon cancer development in mice: IL-6 deficiency prevents adenoma in azoxymethane-treated Smad3 knockouts. (13th January 2016) - Harpel, Kaitlin; Leung, Sarah; Rice, Photini Faith; Jones, Mykella; Barton, Jennifer K; Bommireddy, Ramireddy
Abstract: The development of colorectal cancer in the azoxymethane-induced mouse model can be observed by using a miniaturized optical coherence tomography (OCT) imaging system. This system is uniquely capable of tracking disease development over time, allowing for the monitoring of morphological changes in the distal colon due to tumor development and the presence of lymphoid aggregates. By using genetically engineered mouse models deficient in Interleukin 6 (IL-6) and Smad family member 3 (Smad3), the role of inflammation on tumor development and the immune system can be elucidated. Smad3 knockout mice develop inflammatory response, wasting, and colitis associated cancer while deficiency of proinflammatory cytokine IL-6 confers resistance to tumorigenesis. We present pilot data showing that the Smad3 knockout group had the highest tumor burden, highest spleen weight, and lowest thymus weight. The IL-6 deficiency in Smad3 knockout mice prevented tumor development, splenomegaly, and thymic atrophy. This finding suggests that agents that inhibit IL-6 (e.g. anti-IL-6 antibody, non-steroidal anti-inflammatory drugs [NSAIDs], etc.) could be used as novel therapeutic agents to prevent disease progression and increase the efficacy of anti-cancer agents. OCT can also be useful for initiating early therapy and assessing the benefit of combination therapy targeting inflammation.